Accommodating sampling location uncertainty in continuous phylogeography. Issue 1 (18th May 2022) - Dellicour, Simon; Lemey, Philippe; Suchard, Marc A; Gilbert, Marius; Baele, Guy
Abstract: Phylogeographic inference of the dispersal history of viral lineages offers key opportunities to tackle epidemiological questions about the spread of fast-evolving pathogens across human, animal and plant populations. In continuous space, i.e. when locations are specified by longitude and latitude, these reconstructions are however often limited by the availability or accessibility of precise sampling locations required for such spatially explicit analyses. We here review the different approaches that can be considered when genomic sequences are associated with a geographic area of sampling instead of precise coordinates. In particular, we describe and compare the approaches to define homogeneous and heterogeneous prior ranges of sampling coordinates.